Ação alelopática de extratos de Duranta erecta L. em sementes de Lactuca sativa L. - Moreira, Letícia Leite (2018)
Duranta erecta L. belongs to the Verbenaceae family and comprises species that are distributed in tropical and subtropical regions and which may exhibit the allelopathic effect due to secondary compounds that often do not allow other plants to grow around them. This species has in the literature reports of the presence of secondary metabolites such as alkaloids, flavonoids, acetophenone, coumarin, iridoids, diterpenes, triterpenes, saponins, glycines, phenolic glycosides and steroids; these compounds are important for the development and survival of plants acting as allelopathic or allelochemical compounds. Allelopathy is the influence of one individual on the other, either harming or favoring and it can be tested by means of bioassays using various parameters. Lactuca Sativa L. is a test plant used in bioassays because of its sensitivity to chemical agents, rapid germination, low sensitivity to variation of osmotic potentials and pH. This dissertation is presented in the form of chapters so that chapter 1 presents a brief review on the botanical characterization of Duranta erecta L., secondary metabolites of Duranta erecta L., allelopathy and chemoecology: plant / plant interaction, prune pruning gold, organic agriculture and the use of allelochemicals as bioherbicides, bioassays with Lactuca sativa L. and plant extracts. Chapter 2 is presented in the form of Article I and Article II. In article I, the objective was to study the phytotoxic properties of the leaves of Duranta erecta L. under two management forms (pruning and without pruning) in L. sativa L. using hot and cold aqueous extracts. The significant difference between the extraction methods and the management methods on the allelopathic effect on germination and initial growth of L. sativa L. was verified. The percentage of germination was affected 100% in the highest concentrations, and the germination speed was reduced in all treatments and initial growth of lettuce seedlings were drastically impaired, presenting several morphological abnormalities. The hot aqueous extract of D. erecta L. leaves underwent pruning significantly reduced germination and initial growth parameters. Article II had the purpose of studying the phytotoxic and cytogenotoxic properties of leaves and fruits of Duranta erecta L. using two forms of aqueous and ethanolic extraction. The aqueous and ethanolic extracts of leaves and fruits of Duranta erecta L. presented a phytotoxic effect on L. sativa L., since there was a reduction in the parameters of germination, initial growth and cellular proliferation when compared to the control.